(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Software-defined radio (SDR) is leading concept nowadays, for development of multifunctional radio systems. Article addresses design and implementation on SDR platform of digital modulator/demodulator (modem) with pi/4 differential quadrature phase shift keying modulation (pi/4-DQPSK) and antenna diversity in the receiver side. A model of the system was created in GNU Radio Framework. Experimental results of bit error rate (BER) in presence of additive white Gaussian noise (AWGN) is obtained through simulation and compared with no diversity system. Superiority of diversity scheme, based on criteria BER, is confirmed by numerical results. An experimental, model-based RF DQPSK modem was implemented with Universal Software Radio Peripheral (USRP) frontend. This step from development process confirms advantages of SDR concept, verifies model implementation trough ability to exchange digital information from the transceiver to the receiver in indoor environment and capability of constructive elements to support cocherense. For future implementation of full functional radio communication system, the need of additional blocks for synchronization is identified.